Significance of the Cytological Signs of Human Papillomavirus Infection in Anal Pap Smears of Human Immunodeficiency Virus-Infected Japanese Men Who Have Sex with Men - Okayama, Kaori (Asian Pac J Cancer Prev, 2017)
PURPOSE: The incidence of invasive anal cancer (IAC) has been increasing among human immunodeficiency virus (HIV)-positive men who have sex with men (MSM). Although cytological diagnosis is the modality of choice for screening cases of IAC, it is associated with lower sensitivity and specificity. Therefore, the present study aimed to evaluate new cytological signs of human papillomavirus (HPV) infection that may contribute to improving anal cytology. METHODS: Anal cytology and HPV testing were performed using SurePath liquid-based cytology on samples obtained from 37 HIV-positive Japanese MSM. Subsequently, a histological biopsy based on high-resolution anoscopy was performed in MSM with abnormal cytological findings indicative of atypical squamous cells of undetermined significance (ASC-US) +. Also, anal Papanicolaou (Pap) smears were performed to determine cellularity, presence of dysplastic squamous cells, and other cytological signs of HPV infection. RESULTS: Of the 37 MSM who underwent anal cytology, six tested negative for intraepithelial lesion or malignancy, three cases exhibited ASC-US, 17 exhibited low-grade squamous intraepithelial lesion (LSIL), nine exhibited high-grade squamous intraepithelial lesion (HSIL), and two remained undiagnosed. The anal Pap smears of 28 (96.6%) of the 29 MSM with abnormal cytological findings of ASC-US+ exhibited anal intraepithelial neoplasia (AIN), as revealed by histological biopsy. The median value (minimum–maximum) of the cellularity of anal Pap smears was 12 (0–70.5) nsc/hpf. In 26 MSM with LSIL and HSIL, the median dysplastic squamous cells count was 14 (2–152) dsc/smear and the cytological sign of HPV infection was 11 (2–71) hpv/smear. Of all anal Pap smears that revealed ASC-US+, 96.6% exhibited cytological signs of HPV infection. Compression-positive binucleated cells were the most prevalent among all cytological signs of HPV infection. CONCLUSION: For anal cytology, instead of considering a small number of dysplastic squamous cells, screening based on cytological signs of HPV infection may be beneficial for improving the diagnosis of AIN.